Cepljenje kot pogoj za opravljanje dela - Mežnar, Špela (Delavci in delodajalci, 2022)
The article analyses the legal regulation of mandatory vaccination in the workplace in Slovenia. The author briefly presents the measures taken by some foreign countries during the COVID-19 pandemic, the Constitutional Court's decision U-I-210/21, and highlights some open questions. In the author's opinion, the current legal framework adequately protects the interests that may be in conflict in the case of mandatory vaccination of employees: the interests of public health, employers and employees.
Keywords: cepljenje zaposlenih; Communicable Diseases Act; COVID-19; health anf safety measures at work; mandatory vaccination; obvezno cepljenje; vaccination in the workplace; varnost in zdravje pri delu; zakon o nalezljivih boleznih